New insights into the colony refinement mechanism by solute boron atoms in Ti-6Al-4V alloy. (June 2023) - Chong, Yan; Gholizadeh, Reza; Yamamoto, Kaichi; Tsuji, Nobuhiro
Abstract: The coarse lamellar microstructure of as-cast α + β titanium alloys can be effectively refined by boron additions, which has mainly been attributed to the precipitation of TiB whiskers that pin the growth of prior β grains. Here, we report an alternative mechanism of colony refinement in Ti-6Al-4V alloy containing trace amounts of boron solutes (0.02 wt.%). Using atom probe tomography, it is discovered for the first time that boron solutes segregate at the α / β phase boundaries, due to its negligible solubilities in both α and β phases. These segregated boron solutes at the α / β phase boundaries restrict an easy growth of grain boundary α, and in turn promote the nucleation of more grain boundary α variants that serve as nucleation sites of α colonies. Hence, the colony size can be substantially refined without the formation of TiB whiskers that could be harmful to the ductility of the material. Graphical abstract: Image, graphical abstract